2020
DOI: 10.1111/dth.13525
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive overview of COVID ‐19 based on current evidence

Abstract: In December 2019, twenty-seven pneumonia patients with unknown causes originated in South China seafood market in Wuhan. The virus infection spread rapidly and swept through China in less than a month. Subsequently, the virus was proven a novel coronavirus and named SARS-CoV-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 41 publications
(44 reference statements)
0
28
0
2
Order By: Relevance
“…From March 15 to March 30, 2020, there were 4.7 times increase in reported global cases, taking the total global cases from 167,500 to 782,400 in a matter of weeks (Kaul 2020). During this time, the United States was recording unprecedented rates of viral spread, with over 25,000 new cases per day at the beginning of April (Kang and Xu 2020).…”
Section: Epidemiologymentioning
confidence: 99%
“…From March 15 to March 30, 2020, there were 4.7 times increase in reported global cases, taking the total global cases from 167,500 to 782,400 in a matter of weeks (Kaul 2020). During this time, the United States was recording unprecedented rates of viral spread, with over 25,000 new cases per day at the beginning of April (Kang and Xu 2020).…”
Section: Epidemiologymentioning
confidence: 99%
“…COVID-19 is a globally spread disease, which attacks almost all countries. [ 1 4 ] Studies reported that patients who experience or cured with COVID-19 often have PD. Thus, it is very important to manage such condition.…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus Disease 2019 (COVID-19) is a rapid, global spread virus, [ 1 4 ] which attacks people in almost all countries worldwide. [ 5 8 ] So far, only its transmission in China has been controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Community hospitals refer to medical institutions that provide basic medical services, general hospitals refer to medical institutions that have no restrictions on the scope of disease treatment, and specialist hospitals refer to medical institutions that have certain restrictions on the scope of disease treatment. To study the impact of the distance between a hospital and the infection source on HCW infections, we further calculated the straight-line distance between each hospital and the South China Seafood Market [29]; the calculated results are represented by the "distance" throughout this work.…”
Section: Study Area and Data Sourcesmentioning
confidence: 99%